2019
DOI: 10.1590/1807-3107bor-2019.vol33.0049
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of bioceramic and epoxy-resin endodontic cements into lateral canals

Abstract: Ilana Thaís de Freitas LIMA (a) Bruno Carvalho de VASCONCELOS (c) Nilton Vivacqua GOMES (b) Elaine Faga IGLECIAS (d) Giulio GAVINI (d)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
0
12
1
3
Order By: Relevance
“…In addition, most of the studies that evaluated root canal filling used root canals of extracted human teeth, whereas in the present study it was used simulated canals in blocks of acrylic resin [28][29][30]. Although the artificial canals do not reproduce the characteristics of root dentin, there is a great difficulty in obtaining human teeth with similar conditions for comparison [36]. Therefore, laboratory studies with acrylic blocks and simulated canals are commonly used, which ensure a control of experimental conditions, allowing only the variables of interest to be analyzed [37,38].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, most of the studies that evaluated root canal filling used root canals of extracted human teeth, whereas in the present study it was used simulated canals in blocks of acrylic resin [28][29][30]. Although the artificial canals do not reproduce the characteristics of root dentin, there is a great difficulty in obtaining human teeth with similar conditions for comparison [36]. Therefore, laboratory studies with acrylic blocks and simulated canals are commonly used, which ensure a control of experimental conditions, allowing only the variables of interest to be analyzed [37,38].…”
Section: Discussionmentioning
confidence: 96%
“…Periapical radiographs were taken and a scale from 0 to 4 was used to assess the penetration of the sealer into the root canals. It was observed that Endosequence BC Sealer showed similar ability to penetrate lateral canals as AH Plus [10].…”
Section: Editorialmentioning
confidence: 98%
“…Candeiro, et al, studied the penetration ability of two endodontic cements (Endosequence BC Sealer and AH Plus) using 26 maxillary premolars that had 2 canals. Six lateral canals with two diameters (0.06 and 0.10 mm) were created in each root and filled with single crowns [10]. The teeth were divided into two groups; the first group used Endosequence BC Sealer and the second, AH Plus.…”
Section: Editorialmentioning
confidence: 99%
“…Еще одно их положительное свойство -значительно лучшая герметизирующая способность, чем у других силеров [51][52][53]. Однако многие авторы в своих работах показывают отсутствие разницы в степени проникновения красителя в каналах, обтурированных биокерамическим герметиком и силером на основе эпоксидной смолы [54][55][56].…”
Section: адгезия к филлеру и дентинуunclassified